You are on page 1of 1

Tmath 307 Winter 2013

Picard Iteration Example


Suppose we have the following initial value problem:
(
y 0 = t2 + y 2
y(1) = 2
Then we can integrate both sides and get an equivalent integral equation:
Z t
y(t) = 2 +
s2 + y(s)2 ds
1

Starting with the initial guess solution of 0 (t) = 2, Picard iteration gives
Z t
1 (t) = 2 +
s2 + 0 (s)2 ds
Z1 t
= 2+
s2 + 22 ds
"1
t #

s3
= 2+
+ 4s
3
s=1
 3
  3

t
1
= 2+
+ 4t
+41
3
3
t3
17
=
+ 4t +
3
3
Using this as our new approximation of y(t), we plug it back into the integral equation
and we have
Z t
2 (t) = 2 +
s2 + 1 (s)2 ds
1
2
 3
Z t
s
17
2
+ 4s +
ds
= 2+
s +
3
3
1
Z t
s6 /9 + (8s4 )/3 + (34s3 )/9 + 17s2 + (136s)/3 + 289/9 ds
= 2+
h1
t i
= 2 + (289s)/9 + (68s2 )/3 + (17s3 )/3 + (17s4 )/18 + (8s5 )/15 + s7 /63 s=1

= 2 + (289t)/9 + (68t2 )/3 + (17t3 )/3 + (17t4 )/18 + (8t5 )/15 + t7 /63
(289/9 + 68/3 + 17/3 + 17/18 + 8/15 + 1/63)
t7
8t5 17t4 17t3 68t2 289t 12587
=
+
+
+
+
+

63
15
18
3
3
9
210
and so on. . .
Z t
3 (t) = 2 +
s2 + 2 (s)2 ds = . . .
1

This doesnt look like its converging to anything, but it can be shown that this converges
for some open set (t h, t + h).